A psychometric evaluation of the group environment questionnaire in a sample of professional basketball and soccer players - Steca, P.; Norcini Pala, A.; Greco, A.; Monzani, D.; D'Addario, M. (Perceptual and Motor Skills, 2013)
Psychometric properties of the Group Environment Questionnaire were investigated in a large sample of soccer (n = 222) and professional basketball players (n = 375). Confirmatory factor analysis was performed both on the total sample and on the two subsamples through a multi-group approach; associations between cohesion and the duration of belonging to the team were also explored. Results confirmed the four-factor structure proposed by Carron's original model even though some items with low loadings were eliminated. No significant associations were found between team cohesion and the duration of belonging to the team.